(untitled) (Journal of Engineering, 2022)
The waste material problem in today’s world has become a major topic affecting all sectors of human life. Researchers are interested in providing solutions for each kind of waste material. Waste glass is one of the waste materials whose amounts increase daily. This article deals with two types of modified cement mortar with glass granular in the masonry wall to find their effect on the wall’s property (direct tensile, flexural, and compressive bond strength). Seven different mixes were prepared according to the used glass granular ratio (three mixes contained white glass with 15, 20, and 25% while three of them contained green glass granular 5, 10, and 15%, and the last mix was a controlled mix which contains no glass granular).Based on the obtained result, the used white glass granular provides optimum compression and direct tensile bond strength when 20% of sand is replaced with white glass granular; optimum direct tensile bond value was obtained, which increased by 1.4% and increased compressive strength by 13.08% compared to control mortar. Green glass granular provides optimum compression and direct tensile bond strength when 10% of sand is replaced, direct tensile strength by 1.02%, and increased compressive strength by 3.7% compared to control mortar. The increase of the used waste glass granular in the mortar decreases flexural bond strength, and the amount of decrease depends on the chemical glass compositions.